Chondro-osseous respiratory epithelial adenomatoid hamartoma of the nasal cavity - Fedda,Faysal (2013)
INTRODUCTION: Chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH) is a benign lesion of the nose and sinuses that is extremely rare, with only 2 cases reported in the literature to date. CASE REPORT: We present herein the third reported case of COREAH, in a 38-year-old woman who presented with left nasal obstruction and a mass in her left nasal cavity. The mass was completely resected endoscopically. Microscopic examination showed hamartomatous proliferation of respiratory-type glands with mucinous metaplasia admixed with numerous spicules of mature bone, characteristic of COREAH. CONCLUSION: COREAH is a benign hamartomatous proliferation of respiratory epithelium, submucosal glands, and chondro-osseous mesenchyme. The clinical differential diagnoses for such lesions include glandular hamartoma, inflammatory polyp, inverted papilloma, and low-grade sinonasal adenocarcinoma. Recognition of this lesion as benign despite its potentially worrisome radiographic appearance is important to avoid an unnecessarily radical surgical procedure.